Characterization of vacuum brazed advanced ceramic and composite joints - Jacobson, Logan (University of Wisconsin--Stout. Research Services, 2014)
The microstructure and hardness of nineteen vacuum brazed joints of zirconium diboride and silicon nitride made using a variety of braze alloys were evaluated. Samples were cut and mounted in epoxy, ground and polished, tested for Knoop hardness, and examined for joint microstructure using optical microscopy. Select multilayer joints were examined in depth for microstructure and composition using scanning electron microscopy and energy dispersive spectroscopy. Directly bonded zirconium diboride (ZrB2) led to better quality joints than directly bonded silicon nitride (Si3N4). The larger thermal expansion coefficient of Si3N4 than ZrB2 led to greater expansion mismatch and a higher propensity for cracking in Si3N4 joints. The incidence of cracking in Si3N4 joints decreased with the use of tungsten, molybdenum and tantalum interlayers. The joints made using Ticontaining braze alloys exhibited Ti enrichment of the interface. The hardness distribution mimicked the stacking sequence of the interlayers.
Research article with tables, illustrations, and graphs.
Keywords: ceramic joint; composite joint; Vacuum brazing; Ceramic materials; Composite materials